Enhancing goalkeeper reaction speed in football: The impact of ball launcher training in physical training methods - Supriadi, Amir; Mesnan; Azandi, Filli; Destya, Muhammad Reza; Farooque, S M (UIR Press, 2023)
The football goalkeeper position arguably represents a unique role in team sports. This research aimed to increase the reaction speed of football goalkeepers using a ball launcher. The research method was experimental using a one-group pretest-posttest design. The research was conducted by applying reaction speed training using a ball launcher to measure and found out the results of the data obtained by researchers using the Statistical Package for the Social Sciences (SPSS) software. The research sample consisted of 20 students of the Department of Sports Coaching Education at Universitas Negeri Medan who specialised as football goalkeepers. The instrument used in data collection techniques was the Nelson Foot Reaction. The data analysis technique used was a t-test with a significance level of 0.05. The research results concluded that there was a significant effect of training using a ball launcher on the reaction speed of the goalkeeper. The results can be used as a basis for developing more effective and innovative training methods in the sport of football. In addition, the findings can provide guidance for coaches and researchers in developing relevant and efficient training methods. This study also opens the door for further research to explore the impact of reaction speed in actual match situations, which may yield further insights into the development of quality goalkeeping athletes.